Penerapan Media Megasiz (Media Game Edukasi Quizizz) Untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas V SD Negeri 13 Mataram Tahun Pelajaran 2022/2023 - Yuniani, Ni Kadek Dwi; Rahmaputri, Olliviani; Rohyani, Helmi; Arjudin, Arjudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This classroom action research aims to improve learning outcomes in Mathematics learning through MEGASIZ learning media (Quizizz educational game media) for class V students at SD Negeri 13 Mataram. The type of research is classroom action research (PTK) and uses a descriptive quantitative approach. This research was carried out at SD Negeri 13 Mataram. The research subjects were all class V students consisting of 34 students. The object of research is the learning outcomes of students. The research was implemented in three cycles and carried out collaboratively between researchers and tutors. Data collection techniques use tests and observation sheets. The results of this research show that the application of MEGASIZ media (quizizz educational game media) in learning, especially as an evaluation tool, can improve the learning outcomes of class V students at SD Negeri 13 Mataram. This increase is shown in the quality of the learning process which produces activeness, enthusiasm and enthusiasm as well as test scores on student learning outcomes. Improvement can also be seen from the average score of students' test results from pre-action to cycle II. In pre-action, the average student score was 64, increased in cycle I to 73, then increased again in cycle 2 to 77. The percentage of completion from cycle I and cycle II was 58.82% (20 students) respectively, increasing in second cycle to 79.41% (27 students). Because the completion criteria have been achieved, namely 75% of students obtained a score above or equal to the KKM (75), this research is said to be successful.